Simultaneous detection of SARS-CoV-2 and Influenza virus in wastewater of two cities in Southeastern Germany, january to may 2022 - Dumke, Roger; Geissler, Michael; Skupin, Annett; Helm, Björn; Mayer, Robin; Schubert, Sara; Oertel, Reinhard; Renner, Bertold; Dalpke, Alexander (International journal of environmental research and public health, 2022)
Dependent on the excretion pattern, wastewater monitoring of viruses can be a valuable approach to characterizing their circulation in the human population. Using polyethylene glycol precipitation and reverse transcription-quantitative PCR, the occurrence of RNA of SARS-CoV-2 and influenza viruses A/B in the raw wastewater of two treatment plants in Germany between January and May 2022 was investigated. Due to the relatively high incidence in both exposal areas (plant 1 and plant 2), SARS-CoV-2-specific RNA was determined in all 273 composite samples analyzed (concentration of E gene: 1.3 × 104 to 3.2 × 106 gc/L). Despite a nation-wide low number of confirmed infections, influenza virus A was demonstrated in 5.2% (concentration: 9.8 × 102 to 8.4 × 104 gc/L; plant 1) and in 41.6% (3.6 × 103 to 3.0 × 105 gc/L; plant 2) of samples. Influenza virus B was detected in 36.0% (7.2 × 102 to 8.5 × 106 gc/L; plant 1) and 57.7% (9.6 × 103 to 2.1 × 107 gc/L; plant 2) of wastewater samples. The results of the study demonstrate the frequent detection of two primary respiratory viruses in wastewater and offer the possibility to track the epidemiology of influenza by wastewater-based monitoring.